Quality of life and risk factors that affect the quality of life of Thai female physicians - Teraporn Vutyavanich (2018)
Objective: To study the quality of life (QOL) and risk factors that affect QOL of Thai female physicians. Material and Method: The Thai version of the brief form of WHO quality of life assessment instrument (WHOQOL-BREF-THAI) and risk assessment questionnaires were mailed to 1,700 randomly selected female physicians. Results: The authors obtained a response rate of 41.9%. Most physicians were married (57.3%), they worked 57.3 hours/week, and had a mean income of 64,622 baht/month. The prevalence of obesity was 12.6%. Most (99.3%) did not drink alcohol, 69.6% avoided high cholesterol and a fat diet, 65.8% consumed a balanced diet, and 55.9% included vegetables and fruit in half of their meals. The majority (62.2%) exercised for less than 30 min/day. They used a safety belt (92.1%) or crash helmet (87.5%) when driving a motor vehicle. Regarding their current health, 8.9% had hearing problems, 6.1% had diabetes, 3.3% had glaucoma, and 1.8% had hypertension. Conclusion: Most female physicians had fair to good QOL scores. They were health and safety conscious. These aspects can be used in a campaign to promote a healthier life-style for Thai women.